2015
DOI: 10.3109/03091902.2015.1048317
|View full text |Cite
|
Sign up to set email alerts
|

Chaos–chaos transition of left hemisphere EEGs during standard tasks of Waterloo-Stanford Group Scale of hypnotic susceptibility

Abstract: A recent study, recurrence quantification analysis of EEG signals during standard tasks of Waterloo-Stanford Group Scale of hypnotic susceptibility investigated recurrence quantifiers (RQs) of hypnotic electroencephalograph (EEG) signals recorded after hypnotic induction while subjects were doing standard tasks of Waterloo-Stanford Group Scale (WSGS) of hypnotic susceptibility to distinguish subjects of different hypnotizability levels. Following the same analysis, the current study determines the capability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…This finding fits with the idea advanced by References [70,71] of higher cognitive flexibility in HS, as compared to LS, in waking state, and with the higher involvement at the left fronto-limbic level, of the focused attention control system in HS both during the waking-resting phase and the initial stage of the hypnotic induction process [72][73][74]. This result could also be considered in line with [26], in which authors found a higher left hemisphere EEG chaotic activity than in the right one, in distinguishing HS from MS and LS subjects. Additionally, we have also found that HS and LS differed in terms of LZC for Pz.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This finding fits with the idea advanced by References [70,71] of higher cognitive flexibility in HS, as compared to LS, in waking state, and with the higher involvement at the left fronto-limbic level, of the focused attention control system in HS both during the waking-resting phase and the initial stage of the hypnotic induction process [72][73][74]. This result could also be considered in line with [26], in which authors found a higher left hemisphere EEG chaotic activity than in the right one, in distinguishing HS from MS and LS subjects. Additionally, we have also found that HS and LS differed in terms of LZC for Pz.…”
Section: Discussionsupporting
confidence: 90%
“…In the view of identifying more specific markers of hypnotic susceptibility, additional studies applied nonlinear measures to EEG of subjects under hypnosis [21][22][23][24][25][26]. In particular, it was observed that complexity was higher among HS compared to MS and LS using both Recurrence Quantification Analysis (RQA) and Fractal Dimension Analysis (FDA) [21,25].…”
Section: Introductionmentioning
confidence: 99%
“…Within each three-minute-long window (i.e., R OE , R CE , IND1, IND2, NH, POST), we estimated the PSD with the Welch method using five-second-long windows with an overlap of 80%. The PSD was then integrated in the canonical EEG frequency bands, i.e., delta (1-4 Hz), theta (4-8 Hz), alpha (8-12 Hz), beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and gamma (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45).…”
Section: Signal Acquisition and Analysismentioning
confidence: 99%
“…At the end of hypnotic induction scaling exponents decreased in all groups. In a later study, Yargholi and Nasrabadi used the recurrence quantification (RQ) analysis of the EEG recording data of the above-mentioned study obtained during the 12 suggestibility tests of the WSGS and showed that left hemisphere recordings were more efficient in distinguishing subjects with different hypnotic susceptibility than those of the right hemisphere [135].…”
Section: Nonlinear Dynamical Analysis Of the Eegmentioning
confidence: 99%